Real-Ear-to-Coupler Difference Predictions as a Function of Age for Two Coupling Procedures - Bagatto, Marlene P.; Scollie, Susan D.; Seewald, Richard C.; Moodie, K. Shane; Hoover, Brenda M. (Journal of the American Academy of Audiology, 2002)
The predicted real-ear-to-coupler difference (RECD) values currently used in pediatric hearing instrument prescription methods are based on 12-month age range categories and were derived from measures using standard acoustic immittance probe tips. Consequently, the purpose of this study was to develop normative RECD predicted values for foam/acoustic immittance tips and custom earmolds across the age continuum. To this end, RECD data were collected on 392 infants and children (141 with acoustic immittance tips, 251 with earmolds) to develop normative regression equations for use in deriving continuous age predictions of RECDs for foam/acoustic immittance tips and earmolds. Owing to the substantial between-subject variability observed in the data, the predictive equations of RECDs by age (in months) resulted in only gross estimates of RECD values (i.e., within ± 4.4 dB for 95% of acoustic immittance tip measures; within ± 5.4 dB in 95% of measures with custom ear molds) across frequency. Thus, it is concluded that the estimates derived from this study should not be used to replace the more precise individual RECD measurements. Relative to previously available normative RECD values for infants and young children, however, the estimates derived through this study provide somewhat more accurate predicted values for use under those circumstances for which individual RECD measurements cannot be made.
Keywords: Amplification for children; predicted values; real-ear-to-coupler difference; real-ear measurements